2016
DOI: 10.1021/acscatal.5b02950
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Surface-Assembly of Nanoscale Leaf-Type Cu-Oxide Electrocatalyst for High Activity Water Oxidation

Abstract: ABSTRACT:The controlled surface deposition of a robust and highperformance nanostructured copper-oxide (CuO x -NLs) electrocatalyst for water oxidation is presented. The material exhibits a characteristic leaf-type morphology and self-assembles on a copper substrate by straightforward constant-current anodization. The oxygen onset occurs at about 1.55 V versus RHE (η = 320 mV), which is 400−500 mV less than for amorphous Cu-oxide films. A Tafel slope of 44 mV dec −1 is obtained, which is the lowest observed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 29 publications
4
65
1
Order By: Relevance
“…The formation of a thin layer of (oxy)hydroxide was also observed with the appearance of a characteristic new peak at approximately 595 cm −1 (Figure S15 in the Supporting Information) in the Raman spectrum, which represents the collective vibration of the B g mode of oxygen in the metal‐(oxy)hydroxide owing to the change in their polarizability . The sensitivity of this collective vibration coupled with the electronic charge/state may result in the structural/electronic flexibility, which could facilitate the polarization of water molecules and electron transfer during catalysis . We believe that such a competent and sustained behavior is most likely owing to the inherently generated optimum redox potential induced by the interconvertible redox couple (Co 0/2+/3+ ) .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The formation of a thin layer of (oxy)hydroxide was also observed with the appearance of a characteristic new peak at approximately 595 cm −1 (Figure S15 in the Supporting Information) in the Raman spectrum, which represents the collective vibration of the B g mode of oxygen in the metal‐(oxy)hydroxide owing to the change in their polarizability . The sensitivity of this collective vibration coupled with the electronic charge/state may result in the structural/electronic flexibility, which could facilitate the polarization of water molecules and electron transfer during catalysis . We believe that such a competent and sustained behavior is most likely owing to the inherently generated optimum redox potential induced by the interconvertible redox couple (Co 0/2+/3+ ) .…”
Section: Resultsmentioning
confidence: 83%
“…[40] The sensitivity of this collective vibration coupled with the electronic charge/state may result in the structural/electronic flexibility,w hich could facilitate the polarization of water molecules and electron transfer during catalysis. [41] We believe that such ac ompetent and sustained behavior is most likely owing to the inherently generated optimum redox potentiali nduced by the interconvertible redox couple (Co 0/2 + /3 + ) . Moreover,t he large number of active sites on the surfaceo ft he ultrasmall supported NCs and their stable/regeneratable behavior are highly regarded to propel the fast transport of electrons (4 e À )b etween the catalysta nd adsorbed speciesf or the dynamic release of O 2 molecules with high selectivity.…”
Section: Electrochemical Water-oxidation Catalysismentioning
confidence: 99%
“…It is anticipated that this investigation will further advance the knowledge and methods to prepare robust and high activity catalytic materials for anodic water splitting. 61 …”
Section: Discussionmentioning
confidence: 99%
“…Representative linear sweep voltammograms (LSV) in 1.0 m aqueous NaOH solution are shown in Figure 4. To assess the influence of the high electrochemical surface area (ECSA) of studied materials (values given in the Supporting Information, Table S3) on their catalytic properties,w en ormalized the LSV plots by the ECSA of the electrodes (Supporting Information, Figure S8) and compared them to as tate of the art porous copper oxide OER catalyst [14] (Supporting Information, Figure S9). To assess the influence of the high electrochemical surface area (ECSA) of studied materials (values given in the Supporting Information, Table S3) on their catalytic properties,w en ormalized the LSV plots by the ECSA of the electrodes (Supporting Information, Figure S8) and compared them to as tate of the art porous copper oxide OER catalyst [14] (Supporting Information, Figure S9).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1][2][3] However,t he water oxidation half-reaction, also called the oxygen evolution reaction (OER), providing the electrons required for proton reduction, implies the loss of four electrons and four protons from two water molecules with concomitant formation of an O À O bond. [11][12][13][14][15][16][17] While these are still outperformed by state of the art catalysts [6][7][8][9][10] (Supporting Information, Tables S1 and S2), the low cost and large abundance of copper justifies pursuing studies on rationally designed copper oxide electrodes. [4][5][6][7][8][9][10] In that context, few recent examples have indicated that CuO-based materials electrodeposited from molecular Cu complexes or simple Cu salts could display interesting performances for water oxidation.…”
mentioning
confidence: 99%